Learn Japanese with manga an intermediate self-study language guide - Bernabe, Marc (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2023)
"If you enjoy manga, you'll love learning Japanese with this book. The language lessons are interspersed with entertaining manga comic strips that make it easy to learn and remember all the key vocabulary and grammar. The plot picks up where Learn Japanese with Manga Volume 1 left off, following Nuria, a journalist who is sent to Tokyo to research a news story, where she keeps encountering a mysterious 'shadow' or kage"--Publisher's description.